2014
DOI: 10.1111/jfpe.12110
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Water Treatment for Producing Seasoning From Semidried Isada Krill

Abstract: Semidried Isada krill (Euphausia pacifica) was treated with boiling water and subcritical water at 100-240C for 10 min with a semidried krill to a water ratio of 8/52 w/v to produce seasoning. The protein concentration, lipid content and odor concentration of the extract increased after increasing the treatment temperature. The highest protein content of the extract (0.047-0.049 kg/kg-extract) was obtained by subcritical water treatment at 180 or 200C. Compounds with lower molecular mass were detected in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The strongest shrimp-like fl avour was detected in the extracts and residues prepared at 140-160 °C. These results are similar to those for the treatment of raw krill mixed with water (10). The temperature dependence of preference scores was similar to that of the shrimp-like-fl avour intensity (Fig.…”
Section: Odour Intensity and Sensory Evaluationsupporting
confidence: 77%
See 2 more Smart Citations
“…The strongest shrimp-like fl avour was detected in the extracts and residues prepared at 140-160 °C. These results are similar to those for the treatment of raw krill mixed with water (10). The temperature dependence of preference scores was similar to that of the shrimp-like-fl avour intensity (Fig.…”
Section: Odour Intensity and Sensory Evaluationsupporting
confidence: 77%
“…We have also applied the treatment to semi-dried or raw krill by mixing the krill with water at a mass ratio of 1:1, to produce extracts and residues having pleasant, shrimp-like fl avour (10,11). Using the products as seasoning should be safe regarding fl uoride toxicity because only a small amount will be applied to food products.…”
Section: Issn 1330-9862mentioning
confidence: 99%
See 1 more Smart Citation
“…We also reported that treatment of the semi-dried and raw krill (Koomyart et al, 2015a(Koomyart et al, , 2015b under subcritical water conditions could produce liquid extracts and solid residues with a pleasant flavor, and may be prospective seasoning ingredients.…”
Section: Introductionmentioning
confidence: 92%
“…In the previous reports, we used a small pressure-resistant vessel with an inner volume of 117 mL, and the vessel was heated using either an external mantle heater or by immersion in an oil bath (Koomyart et al, 2015a(Koomyart et al, , 2015b. However, such heating methods would be inadequate or inconvenient for treating the krill in large quantities.…”
Section: Introductionmentioning
confidence: 99%